Tác động của vốn con người đến tăng trưởng kinh tế Đồng bằng sông Cửu Long - Đinh Phi, Hổ; Từ Đức, Hoàng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
The aim of this study is to assess the effects of human capital on the economic growth in Mekong-Delta area via using the panel data (104 observations) of 13 provinces, from 2006 through 2013, and an extended Cobb-Douglas production function. Two regression models for the panel dataset are also employed, including: (i) Random Effects Model (REM), and (ii) Fixed Effects Model (FEM). While the proxies for education are average year of schooling and public education expenditure, the proxy for health is public health expenditure. Besides the main ones in the paper, some other controlled variables such as private investment, poverty rate, trade openness, and non-agricultural rate are included in the model. The estimation results indicate that human capital has a positive and significant effect on growth, leading to possible implications to enhance the regional economic growth.